How Brand Knowledge Affects Purchase Intentions in Fresh Food E-Commerce Platforms: The Serial Mediation Effect of Perceived Value and Brand Trust - Ling, Shuai; Zheng, Can; Cho, Dongmin (Behavioral sciences, 2023)
The intense competition among fresh food e-commerce platforms in China has reduced the market share of the leading firms. This study aims to establish a model framework based on brand knowledge, perceived value, brand trust, and purchase intention to improve the market competitiveness of fresh food e-commerce platforms. Based on the analysis of 475 questionnaires using SmartPLS software, the results indicate that the established model framework provides an excellent explanation and forecasting (R2 = 45.5%) for consumers’ intentions to purchase fresh food. The path analysis results of this study show that there are significant positive effects among the model variables. Among antecedent variables, brand image has the greatest influence on perceived value, perceived value has the greatest influence on brand trust, and brand trust has the most significant impact on purchase intention. Furthermore, perceived value and brand trust have noteworthy mediating and serial mediating effects on brand knowledge and purchase intention. These findings have important implications for theoretical and managerial practices in the context of fresh food e-commerce platforms, providing insights on how to enhance customer purchase intentions.